2020
DOI: 10.1093/femsec/fiaa133
|View full text |Cite
|
Sign up to set email alerts
|

Biochar as electron donor for reduction of N2O by Paracoccus denitrificans

Abstract: Biochar (BC) has been shown to influence microbial denitrification and mitigate soil N2O emissions. However, it is unclear if BC is able to directly stimulate the microbial reduction of N2O to N2. We hypothesized that the ability of BC to lower N2O emissions could be related not only to its ability to store electrons, but to donate them to bacteria that enzymatically reduce N2O. Therefore, we carried out anoxic incubations with Paracoccus denitrificans, known amounts of N2O, and nine contrasting BCs, in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 60 publications
0
10
2
Order By: Relevance
“…In contrast to our findings, Chintala et al (2015) who carried out a one week-incubation using mixtures of soil and fresh BCs reported that the increase in total denitrification was distinctly higher in the control than in BC-treated samples. The differences between the findings of our study and the one by Chintala et al (2015) might be explained by a stronger electron shuttle function of BC in our study highlighting the importance of the properties of the BCs used (Bakshi et al, 2016;Pascual et al, 2020;Yuan et al, 2019).…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…In contrast to our findings, Chintala et al (2015) who carried out a one week-incubation using mixtures of soil and fresh BCs reported that the increase in total denitrification was distinctly higher in the control than in BC-treated samples. The differences between the findings of our study and the one by Chintala et al (2015) might be explained by a stronger electron shuttle function of BC in our study highlighting the importance of the properties of the BCs used (Bakshi et al, 2016;Pascual et al, 2020;Yuan et al, 2019).…”
Section: Discussioncontrasting
confidence: 96%
“…The differences between the findings of our study and the one by Chintala et al. (2015) might be explained by a stronger electron shuttle function of BC in our study highlighting the importance of the properties of the BCs used (Bakshi et al., 2016; Pascual et al., 2020; Yuan et al., 2019).…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Biochar can lower denitrification (the reduction of NO3 to N 2 ) by: (i) facilitating the last step of denitrification (the transformation of N 2 O to N 2 ), and (ii) decreasing total denitrification activity (Cayuela et al, 2013; Weldon et al, 2019). Biochar can facilitate the reduction of N 2 O to N 2 via: (i) increasing pH in acid soils (Obia et al, 2015) thus enhancing the nosZ gene (Harter, Guzman‐Bustamante, et al, 2016); (ii) changing the relative abundance and composition of N 2 O‐reducing microbial communities (Harter, Weigold, et al, 2016); and (iii) facilitating extracellular electron exchange (Chen et al, 2014) or directly donating electrons to denitrifying bacteria (Pascual, Sánchez‐Monedero, Cayuela, et al, 2020). The decrease in denitrification may result from decrease in availability of NO 3 − and bioavailable C substrate (Fiorentino et al, 2019; Hagemann, Kammann, et al, 2017; Heaney et al, 2020).…”
Section: Biochar's Role In Climate Change Mitigationmentioning
confidence: 99%